Development and Evaluation of Unidirectional Mucoadhesive Bio-Flexy Films Loaded with Nanosized Topiramate using a Novel Biopolymer from Glycine max - Varshney, Sugandha; Madhav, N V Satheesh (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: Formulation and evaluation of nanosized Topiramate loaded bio-flexy films using novel biopolymer isolated from Glycine max seeds for epilepsy treatment. Methods: Formulations containing nanosized Topiramate: Glycine max biopolymer (in ratios of 1:0.5, 1:1; 1:3, 1:5, 1:6, 1:10) (FGO1-FGO6) were prepared by solvent casting method. Results: Glycine max biopolymer showed percentage yield: 81.06%±0.01, light yellow, odorless, soluble in chloroform, water and color changing point: 218°C±2. Topiramate loaded bio-flexy films containing Glycine max biopolymer (FGO1-FGO6) revealed Thickness: 0.019 mm±0.012 to 0.037 mm±0.010, Surface pH:7.01±0.03 to 7.01±0.02, ex-vivo Mucoadhesion Time: 30-120 mins, ex vivo Mucoretention Time:90-210 mins, Weight Uniformity: 0.078±0.05 to 0.083±0.04, Drug Content Uniformity:72.7%±0.50 to 82.84%±0.48, Folding Endurance: 117-173, Swelling Percentage: 62%±0.6 to 74%±0.4, Percentage Moisture Uptake (PTU): 2.0%±0.13 to 2.8%±0.12. The drug release pattern based on the T50% and T80% was found to be FGO2 (1:1) > FGO6 (1:10) > FGO1 (1:0.5) > FGO4 (1:5)> FGO5 (1:6) > FGO3 (1:3). Conclusion: Based on all the evaluation parameters, FGO2 (containing Topiramate: Glycine max biopolymer (1:1)) Bio-flexy film having R2=0.9139, Higuchi Matrix as best fit model, follows Fickian Diffusion (Higuchi Matrix) release mechanism, T50%: 25 hr., T80%: 27 hr. Prepared formulations were suitable for Soft Palatal Delivery.
Keywords: Unidirectional; Mucoadhesive; Bio-flexy films; Nanosized Topiramate; Soft; Palate; Glycine max biopolymer